2011
DOI: 10.1055/s-0031-1296177
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study of the novel, synthetic trioxane antimalarial compound 97-78 in rats using an LC-MS/MS method for quantification

Abstract: The present study has been designed to investigate the pharmacokinetic parameters of the novel trioxane antimalarial 97-78 (US Patent 6316493 B1, 2001) in male and female rats after single oral and intravenous administration. The pharmacokinetic profile of 97-78 was investigated in the form of its completely converted metabolite 97-63 after dose administration. Quantification of metabolite 97-63 in rat plasma was achieved using a simple and rapid LC-MS/MS method. The LC-MS/MS method has been validated in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 8 publications
(10 reference statements)
0
18
0
Order By: Relevance
“…HPLC elution was carried out in isocratic mode with mobile phase comprising of 80:20 (v/v) ACN (0.1% formic acid) and ammonium acetate buffer (10 mM, pH 4.0) using a Phenomenex C 18 Columbus (50 mm × 2 mm, 5 m particle size) equipped with a security guard cartridge. Separation was achieved at 450 mL/min flow rate with injection volume of 10 mL [13,14]. Processed sample were maintained in auto sampler at 4 C.…”
Section: Pharmacokinetic Sample Processing and Bioanalysismentioning
confidence: 99%
“…HPLC elution was carried out in isocratic mode with mobile phase comprising of 80:20 (v/v) ACN (0.1% formic acid) and ammonium acetate buffer (10 mM, pH 4.0) using a Phenomenex C 18 Columbus (50 mm × 2 mm, 5 m particle size) equipped with a security guard cartridge. Separation was achieved at 450 mL/min flow rate with injection volume of 10 mL [13,14]. Processed sample were maintained in auto sampler at 4 C.…”
Section: Pharmacokinetic Sample Processing and Bioanalysismentioning
confidence: 99%
“…It has around 50% absolute oral bioavailability. [9] CDRI 97-78 has been found to be safe in healthy human volunteers during single ascending dose safety and pharmacokinetic studies. They also observed that body weight is a significant covariate affecting the clearance of PPQ.…”
Section: Introductionmentioning
confidence: 99%
“…[3] In a study conducted in Cambodian patients by Hung et al, children were found to have a two-fold higher oral clearance (1.85 L/h/kg) and a shorter terminal half-life (13.5 days) than adults. [9,12] Thus, in the present study, we have developed and validated a simple, sensitive and specific LC-ESI-MS/MS method for the simultaneous quantification of PPQ and 97-63 in 100 μL rat plasma using halofantrine as an internal standard (IS). Viewing the emerging resistance to artemisinin derivatives along the Thailand-Cambodia border, there is a need to develop better alternatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But 97/78 emerged as lead compound for excellent pharmacological activity in both in vitro and in vivo malarial models. After successful completion of regulatory preclinical studies compound is currently in phase I clinical trials [18, 19]. …”
Section: Introductionmentioning
confidence: 99%